1965
DOI: 10.3181/00379727-120-30598
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Wild and Albino Mice in Response to Forced Swimming.

Abstract: Enforced swimming of animals has been some experiments, colonic temperatures were utilized by many investigators as a method obtained continuously while the animals of inducing and evaluating physiological and swam, thus weighting the animal by an addipsychological stress. However, the time re-tional 2 g. The mice utilized to obtain these quired to produce a state of exhaustion has cooling curves were not utilized in any other shown considerable variation not only among experiments. Cooling curves were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Sub AnT and Supra AnT ) performed more incremental stages in the lactate minimum test, resulting in an increased lactate minimum success rate after the water environment adaptation period. Although reports have shown that luminosity, time of day and water temperature have an effect on swimming rats 2,3,4,5 , we presented novel data regarding the water environment adaptation period influencing the climbing-swimming pattern prevalence. The fact that studies have not been concerned with the proper water environment adaptation raises questions about its importance on experimental procedures involving swimming rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sub AnT and Supra AnT ) performed more incremental stages in the lactate minimum test, resulting in an increased lactate minimum success rate after the water environment adaptation period. Although reports have shown that luminosity, time of day and water temperature have an effect on swimming rats 2,3,4,5 , we presented novel data regarding the water environment adaptation period influencing the climbing-swimming pattern prevalence. The fact that studies have not been concerned with the proper water environment adaptation raises questions about its importance on experimental procedures involving swimming rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although rodents have a recognized, innate swimming ability 1 , studies have demonstrated that luminosity 2 , water temperature 3,4 and the time of day 5 may influence swimming performance in these animals. Furthermore, a discussion about the water environment adaptation was already initiated 6 , but its relevance remains speculative and untested.…”
Section: Introductionmentioning
confidence: 99%
“…We found that at higher water pressures (keeping water temperature constant at a point of thermoneutrality for the rat-34° C), no rats survived because of an inability to keep their nostrils above the surface (Hughes et al, in press). The jet pressure, like the addition of weight used in most swimming endurance studies, functions to increase the work and energy needed to remain afloat (e.g., Foss & Horvath, 1965;McArdle, 1967;Werboff, Haggett, & Anderson, 1967). As with the use of weights, subtle changes in jet pressure have a drastic effect on swimming performance and suggest a partial explanation for survival differences in recent studies (Rossellini et al 1976).…”
Section: Swimming-cylinder Techniquementioning
confidence: 99%